Electric Smart Solar Car System Based on Android - Nugroho, Dimas; Ubaidillah, Ahmad; Joni, Koko (Jurnal Sistem Telekomunikasi Elektronika Sistem Kontrol Power Sistem dan Komputer, 2021)
Along with the increasing number of motorized vehicles resulting in high pollution, energy efficient cars are needed. solar electric car is one of the car solutions fueled by henamt energy. the use of electric cars is considered more effective, in addition to reducing the use of petroleum fuels, it also does not cause pollution. This research makes solar electric cars using photovoltaic modules, electric cars and batteries. solar cell is a source of electrical energy to drive a DC motor supplied from batteries / batteries. while the battery is a storage place for electrical energy. The charge controller is a tool that functions to control the process of storing electrical power in the battery, the process of using the battery as a source of supplying electrical loads and monitoring the condition of the battery level during the charging and discharging process. for the operation of electric cars, android is equipped with automatic control of voice commands. The result of this research is a solar-powered electric car model that uses voice commands as a steering wheel.